Micro-oxigenation level as a key to explain the variation in the colour and chemical composition of wine spirits aged with chestnut wood staves - Canas, Sara (2021)
A deep knowledge of oxygenation level effect on wine spirits’ ageing is imperative to understand ageing chemistry and to select the most suitable technological option towards quality and sustainability. Following two articles on the same trial, this work focused on colour, total phenolic index (TPI) and basic chemical characteristics of a wine spirit aged in 50 L demijohns with chestnut wood staves together with three micro-oxygenation (MOX) levels. Chromatic characteristics and TPI were monitored over time (8–365 days) while sensory colour, alcoholic strength, acidity, pH and dry extract were assessed at the end of ageing. Results showed that stronger oxygenation promoted significantly faster colour evolution (lower lightness, higher chroma, red, yellow and brown hues) and higher TPI than mild and intermediate oxygenation until 60 days, probably by favouring the leaching of outer wood layers and extraction/degradation of tannins. No significant differences were found between these ageing modalities at 365 days. Outcomes suggest that the stronger MOX is the most suitable modality in terms of quality and sustainability. Significant differences between wine spirits resulting from MOX and control modality (slower colour evolution, lower TPI and dry extract) confirms the oxygen pivotal role in wine spirit’s ageing, particularly in the colour evolution